UNDERSTANDING THE GENESIS OF NONMARINE CALCITE DEPOSITS THROUGH QUADRUPOLE MASS SPECTROMETRIC ANALYSIS OF FLUID INCLUSION GASES - Newman B.D.; Norman D.I.; Gundimeda M.; Levy S.S. (My University, 1996)
Quadrupole mass spectroscopy was used to analyze fluid inclusion volatiles in different types of nonmarine calcites including travertines, phreatic calcretes, hydrothermal vein calcites, and pedogenic calcites. The objectives of the study were to determine if there were any diagnostic or characteristic differences between the inclusion volatiles from the different calcites, and to see if the quadrupole results could be used to understand the processes and environmental conditions that controlled calcite precipitation. The calcites formed under saturated conditions have water-dominated inclusions with well-constrained N2Ar ratios and either CO2 or N2 as the dominant inclusion gas. Some calcretes and travertines were exceptions to the above characteristics, but it is likely that these were subjected to secondary precipitation in an environment different from the primary precipitation phase. Results for the pedogenic calcites are quite different from calcites formed in water-saturated systems. Pedogenic calcites have gas-dominated (water-poor) inclusions, unexpectedly large CH4 contents, low O2 contents, and highly variable N2Ar ratios. The dominance of CH4 and low O2 contents in the pedogenic calcites suggest that anaerobic conditions occurred during at least part of the precipitation process. Scanning electron microscope (SEM) examination of the pedogenic calcites shows fungal remains, bacteria-like forms, and gels from fungi or plant roots. The quadrupole and SEM results suggest pedogenic calcite precipitation occurred as a result of aerobic and, ultimately, anaerobic microbial decay processes.